2011
DOI: 10.1177/1084713811420740
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Translation in Audiology

Abstract: The origins of evidence-based practice (EBP) come largely from clinical medicine. The EBP paradigm provides techniques and procedures to critically examine the abundance of scientific evidence in order to assist clinical decision making and improve the quality, effectiveness, and efficiency of health services received by the public. The desired clinical outcome of EBP is an increase in the number of patients who get treatment of proven quality and effectiveness. The generally agreed-upon definition of EBP is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 98 publications
(152 reference statements)
0
21
0
Order By: Relevance
“…As highlighted in another work by Moodie et al (2011), the existence of clinical practice guidelines that dictate best practices for pediatric HA verification is insufficient to encourage the implementation of these practices among practitioners. Alternatively, a systematic approach to knowledge translation may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted in another work by Moodie et al (2011), the existence of clinical practice guidelines that dictate best practices for pediatric HA verification is insufficient to encourage the implementation of these practices among practitioners. Alternatively, a systematic approach to knowledge translation may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…It is vital to ensure that protocols are as focused as possible and encompass all relevant areas to ensure that clinical practice is evidence-based. An evidence-based approach assists in putting research into clinical practice, improves patient care and promotes standardisation of care (Moodie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Audiological protocols based on evidence-based practice assist in achieving care for patients with proven quality and effectiveness (Moodie et al, 2011). There are various international gold standards regarding early detection and intervention for children with HL (Baldwin, Sutton, Gravel & Low, 2008;British Columbia Early Hearing Programme [BCEP], 2008; Joint Committee on Infant Hearing [JCIH], 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To effectively address the emotional needs of parents of children with hearing loss and support their learning process, professionals may not only need further training in effective communication skills, but also support for learning to implement this skillset in practice. Even when there is clear evidence for best practices, research has shown that an array of challenges can interfere with transfer of knowledge to the practice setting (Moodie et al, 2011).…”
Section: Provider Training Considerationsmentioning
confidence: 99%